PERANCANGAN MOBILE CATALOGUE KERAJINAN KHAS DAERAH SUMATERA SELATAN - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
South Sumatera is one of the provinces in Indonesia that has its own distinctive characteristic especially in the local handicrafts that become an attraction for tourists who visit this region. South Sumatra consists of several district and city areas that have their own distinctive and cultural characteristics. South Sumatera area is quite spacious with a variety of different tourist attractions in each region, requiring a media information that can reach the community widely and as a medium of tourism promotion in the province of South Sumatera. One of the wealth owned by South Sumatera Province is a variety of typical handicrafts from various regions in South Sumatera. The research resulted in the design of the application catalog typical South Sumatera mobile based Android. Mobile Catalogue Typical Crafts South Sumatera will provide information about the share of South Sumatera handicrafts such as songket, batik, jumputan cloth, blongsong cloth, tanjung cloth, and crafts carving typical Palembang.